Do Political Connections Induce More or Less Opportunistic Financial Reporting? Evidence from Close Elections Involving SEC‐Influential Politicians* - Jennings, Ross; Kartapanis, Antonis; Yu, Yong (Contemporary Accounting Research, 2021)
ABSTRACT This study explores close US congressional elections involving politicians who have influence over the SEC to examine the effect of firms' political connections on their financial reporting. This question is important in understanding the overall effect of political connections on financial reporting. Our difference‐in‐differences tests reveal no evidence that firms experiencing a relative increase in political connections report more opportunistically after close elections in anticipation of preferential treatment by the SEC in its enforcement actions. In contrast, we find evidence that these firms report less opportunistically in response to an increase in their connections with SEC‐influential politicians. Further tests show that our findings are unlikely to be driven by capital market pressure, managerial equity incentives, or corporate governance. Overall, our results are consistent with political connections mitigating opportunistic reporting through enhanced scrutiny by the SEC of politically connected firms' financial reporting. Our findings provide new insights into the interactions among political connections, SEC oversight, and financial reporting by showing how politically connected firms alter their financial reporting in anticipation of differential treatment by the SEC.